Evaluating the Effects of Travel Time and Cost on Mode Choice in Transportation System - Ruslan; Firmansyah Rachman; Zulfhazli Abdullah (Popular Scientist, 2025)
Mode choice in transportation is influenced by factors such as comfort, safety, travel time, cost, and reliability, with most commuters in Banda Aceh preferring private vehicles due to flexibility and efficiency. Travel time and travel cost are identified as major barriers preventing people from switching to public transport, which is often considered less attractive. While studies abroad examine elasticity from multiple perspectives, research in Indonesia has mainly focused on vehicle attributes. The objective of this paper is to analyze the elasticity of travel time and travel cost for users of private vehicles and public transportation. The study employs a binary probit model to estimate elasticity values, utilizing data from a Stated Preference survey of transportation users. The results show that both trip attributes and individual characteristics significantly influence transport mode choice. Longer travel distances, higher travel time, and increased operating costs raise the likelihood of choosing public transport, while being male and having higher education also increase the tendency to select it. Conversely, motorcycle ownership strongly favors private mode choice, and holding a valid driver’s license is an important determinant of travel behavior. The elasticity analysis further reveals that reducing travel and access times for the TransK bus could significantly increase its usage, while policies restricting private vehicle use, such as the odd-even system, may also encourage shifts toward public transport. The study concludes that mode choice in Banda Aceh is mainly driven by travel time, with TransK highly responsive to time improvements, while private vehicles dominate despite cost changes. Encouraging public transport use requires faster, more reliable bus services and restrictions on private vehicle advantages.